2015
DOI: 10.1088/0029-5515/55/8/083005
|View full text |Cite
|
Sign up to set email alerts
|

EAST alternative magnetic configurations: modelling and first experiments

Abstract: Heat and particle loads on the plasma facing components are among the most challenging issues to be solved for a reactor design. Alternative magnetic configurations may enable tokamak operation with a lower peak heat load than a standard single null (SN) divertor. This papers reports on the creation and control of one of such alternatives: a two-null nearby divertor configuration. An important element of this study is that this two-null divertor was produced on a large superconducting tokamak as an experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…It has been verified the heat reduction capability by using so called snowflake (SF) divertors [3] on most advanced tokamaks such as TCV [4], NSTX [5] and DIII-D [6]. In 2014, we also demonstrated the effects of applying QSF plasma shape [7]. It was found that in L-mode case the peak heat flux to the divertor target can be effectively reduced to at least by a factor of 1/2.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…It has been verified the heat reduction capability by using so called snowflake (SF) divertors [3] on most advanced tokamaks such as TCV [4], NSTX [5] and DIII-D [6]. In 2014, we also demonstrated the effects of applying QSF plasma shape [7]. It was found that in L-mode case the peak heat flux to the divertor target can be effectively reduced to at least by a factor of 1/2.…”
Section: Introductionmentioning
confidence: 80%
“…1, is negligible after SMBI was turned on. It is proving in reference [7] if controlling the plasma shape to the lower single null quasi-snowflake shape (LQSF), the peak heat load can be reduced to the level of a factor below 1/2 in comparision to the conventianl SN diverted plasma configuration. We further extended this operation to exactly control the shape.…”
Section: Divertor Heat Load Controlmentioning
confidence: 99%
“…Additional properties of the configuration include a significantly longer X-point connection length, leading to an increase in the temperature drop and radiative losses in the SOL, and the presence of additional strike points across which the power exhaust can be partitioned. In recent years, the SFD has been the subject of investigations on several devices [22][23][24][25][26][27][28][29], all of which have provided experimental confirmation of many favorable properties of the configuration. In particular, the SFD was integrated into H-mode scenarios on NSTX (prior to the upgrade).…”
Section: Motivation For Advanced Divertors On Nstx-umentioning
confidence: 99%
“…(6) EAST开展了具备良好热负荷分散功能的稳态 准雪花偏滤器磁面位形放电实验, 成功获得了长脉冲 无ELM高约束等离子体, 并有效地实现了热流分散, 显著降低了偏滤器靶板的峰值热负荷 [54] . (7) EAST研制了环向模数n可以达到4的ITER类 型的共振磁扰动(RMP)系统.…”
Section: 了杂质辐射反馈调节技术 实现了稳态运行下的Elmunclassified